PENGARUH STRES KERJA, PELATIHAN DAN PENDIDIKAN TERHADAP KINERJA KARYAWAN PADA PT KARYASINDO SAMUDRA BIRU SHIPYARD - Chandra, Nivata Kumari; Simanjuntak, Jontro (SCIENTIA JOURNAL, 2021)
The purpose of this study was to determine the effect of job stress, training and education on employee performance of PT Karyasindo Samudra Biru Shipyard. The method used in this research is quantitative causality with multiple linier regression analysis using SPSS version 23. The sample in this study using saturated sampling with the total sample is 106 people. The result show partially the influence of job stress variables is 3,504 greater than t table 1,983 with a significance of 0,001 less than 0,05. the influence of training variables is 6,807 greater than t table 1,983 with a significance of 0,000 less than 0,05. And the influence of education variables is 3,694 greater than t table 1,983 with a significance of 0,000 less than 0,05. Then simultaneously job stress, training and education have an effect of 52,329 greater than 2,69 F table with a significance 0,000 less than 0,05 on employee performance at PT Karyasindo Samudra Biru Shipyard. Conclusion, the job stress partially has a significant effect, the training partially has a significant effect, the Education partially has a significant effect and job stress, training and education have a significant effect on employee performance of PT Karyasindo Samudra Biru Shipyard.